АДМІНІСТРАТИВНЕ РЕГУЛЮВАННЯ СОЦІАЛЬНОЇ СТРУКТУРИ ТАТАРСЬКОГО НАСЕЛЕННЯ (1783 – ПЕРША ЧВЕРТЬ XIX ст.) (Zaporizhzhia Historical Review, 2021)
The article is given devoted the question of the administrative adjusting the Russian government of social structure of the Tatar population in a period from the end of 18 for 20th of a 19 age. The basic task of this policy was including of the Tatar population to the social structure of the Russian empire.